2010
DOI: 10.1111/j.1547-5069.2010.01370.x
|View full text |Cite
|
Sign up to set email alerts
|

Retaining Nurses and Other Hospital Workers: An Intergenerational Perspective of the Work Climate

Abstract: New nurses will benefit from strategies aimed at supporting their career advancement in the workplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 42 publications
2
48
0
Order By: Relevance
“…Previous studies in Western countries have suggested that generational work values and attitudes differ and change as people grow older [27]. Such generational differences in work attitude (e.g., intent to continue working, job satisfaction, intention to quit) were also observed on not only in Western countries' hospital workers and nurses [19,28,29] but also in our participants, Japanese female hospital nurses. The age composition of staff nurses varies with each hospital; thus, our findings on the generation-common risk factors (i.e., effort and over-commitment) and the factors reducing intentions to leave (i.e., money reward, the presence of a role model, and social support) among female hospital nurses will provide fruitful suggestions for managers and employers in hospital workplaces with different age compositions when considering countermeasures to avert nurse turnover.…”
Section: Generation-specific Factorssupporting
confidence: 70%
See 4 more Smart Citations
“…Previous studies in Western countries have suggested that generational work values and attitudes differ and change as people grow older [27]. Such generational differences in work attitude (e.g., intent to continue working, job satisfaction, intention to quit) were also observed on not only in Western countries' hospital workers and nurses [19,28,29] but also in our participants, Japanese female hospital nurses. The age composition of staff nurses varies with each hospital; thus, our findings on the generation-common risk factors (i.e., effort and over-commitment) and the factors reducing intentions to leave (i.e., money reward, the presence of a role model, and social support) among female hospital nurses will provide fruitful suggestions for managers and employers in hospital workplaces with different age compositions when considering countermeasures to avert nurse turnover.…”
Section: Generation-specific Factorssupporting
confidence: 70%
“…The number of employed nursing professionals increased by 0.3 million from continue working, job satisfaction, intention to quit) are also observed among hospital workers and nurses [19,28,29].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations